The equations of motion of the main structure with attached dampers described by standard rheological model - Wielgos, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2011)
A mathematical model of structure with multiple tuned mass dampers (MTMD) is presented in this paper. An important difficulty, connected with these model, is building a global damping matrix of the system. The own proposals of FEM elements describing additional elements attached to the main system in the form of tuned dampers are presented here. The benefits of the new FEM elements are briefly discussed.